Endovascular Occlusion Balloon for Treatment of Superior Vena Cava Tears During Transvenous Lead Extraction: A Multiyear Analysis and an Update to Best Practice Protocol. (August 2019) - Azarrafiy, Ryan; Tsang, Darren C.; Wilkoff, Bruce L.; Carrillo, Roger G.
Abstract : Background: Superior vena cava (SVC) tears are one of the most lethal complications in transvenous lead extraction. An endovascular balloon can occlude the SVC in the event of a laceration, preventing blood loss and offering a more controlled surgical field for repair. An early study demonstrated that proper use of this device is associated with reduced mortality. Thereafter, high-volume extractors at the Eleventh Annual Lead Management Symposium developed a best practice protocol for the endovascular balloon. Methods: We collected data on adverse events in lead extraction from July 1, 2016, to July 31, 2018. Data were prospectively collected from both a US Food and Drug Administration–maintained database and physician reports of adverse events as they occurred. We gathered case details directly from extracting physicians. Confirmed SVC tears were analyzed for patient demographics, case details, and index hospitalization mortality. Results: From July 1, 2016, to July 31, 2018, 116 confirmed SVC events were identified, of which 44.0% involved proper balloon use and 56.0% involved no use or improper use. When an endovascular balloon was properly used, 45 of 51 patients (88.2%) survived in comparison to 37 of 65 patients (56.9%) when a balloon was not used or improperly used ( P =0.0002). Furthermore, multivariate regression modeling found that proper balloon deployment was an independent, negative predictor of in-hospital mortality for patients who experienced an SVC laceration (odds ratio, 0.13; 95% CI, 0.04–0.40; P <0.001). Conclusions: From July 1, 2016, through July 31, 2018, patients undergoing lead extraction were more likely to survive SVC tears when treatment included an endovascular balloon. Abstract : Supplemental Digital Content is available in the text.